Assessing impact of differential symptom functioning on post‐traumatic stress disorder (PTSD) diagnosis. Issue 2 (17th January 2014) - He, Qiwei; Glas, Cees A. W.; Veldkamp, Bernard P.
Abstract This article explores the generalizability of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM‐IV) diagnostic criteria for post‐traumatic stress disorder (PTSD) to various subpopulations. Besides identifying the differential symptom functioning (also referred to as differential item functioning [DIF]) related to various background variables such as gender, marital status and educational level, this study emphasizes the importance of evaluating the impact of DIF on population inferences as made in health surveys and clinical trials, and on the diagnosis of individual patients. Using a sample from the National Comorbidity Study‐Replication (NCS‐R), four symptoms for gender, one symptom for marital status, and three symptoms for educational level were significantly flagged as DIF, but their impact on diagnosis was fairly small. We conclude that the DSM‐IV diagnostic criteria for PTSD do not produce substantially biased results in the investigated subpopulations, and there should be few reservations regarding their use. Further, although the impact of DIF (i.e. the influence of differential symptom functioning on diagnostic results) was found to be quite small in the current study, we recommend that diagnosticians always perform a DIF analysis of various subpopulations using the methodology presented here to ensure the diagnostic criteria is valid in their own studies. Copyright © 2014 John Wiley & Sons, Ltd.